A REVIEW ON PANCHAJEERAKA PAKA INDICATED IN SUTIKA KALA (AYUSHDHARA, 2020)
Health of women reflects status of the society. Pregnancy and childbirth leads to physiological and psychological changes in women. In developing countries, malnutrition, repeated child births, early age conception and other debilitating diseases can hamper mother’s health. Women in post partum period are vulnerable to many disorders some of which may lead to serious condition if left untreated. This can hamper physical as well as mental health. Even though such post partum care has been practicing worldwide, methods, drugs, medication forms varies in accordance with place, climate, availability of drugs etc. Special regimen, dietary preparations and activities are recommended in Ayurveda during Sutika kala (post natal period). Since mother’s health condition generally affects the health of new born, keen care has to be taken for any ailments arousing during post natal period. Main principles in management during normal peurperium include restoring the health of mother, preventing infection and promoting breast feeding. Pancha jeeraka paka is one of the medications in Ayurvedic classics recommended during Puerperium. This article is an attempt to review on Pancha jeeraka paka, its ingredients and possible mode of action in Sutikarogas (diseases occurring during post natal period).